A novel polygeneration process to co-produce ethylene and electricity from shale gas with zero CO2 emissions via methane oxidative coupling. (1st March 2015) - Khojasteh Salkuyeh, Yaser; Adams, Thomas A.
Highlights: Development of an ethylene plant from shale gases with zero CO2 emissions. Oxidative coupling of methane is used for the conversion of gas to ethylene. Polygeneration strategy is used to improve the profitability of plant. Abstract: A techno-economic analysis of a novel process to co-produce ethylene and electricity using a recently developed methane oxidative coupling catalyst is presented. Several design variants are considered, featuring the use of traditional gas turbines, chemical looping combustion, and 100% carbon dioxide capture. Mass and energy balance simulations were carried out using Aspen Plus simulations, and particle swarm optimization was used to determine the optimal process design under a variety of market scenarios. A custom model for the gas turbine section was used to ensure that the negative impacts of various cooling strategies were factored into the analysis. The results show that by synergistically co-producing power and ethylene using this catalyst, ethylene can be produced at costs close to traditional steam cracking methods with nearly zero carbon dioxide emissions, even when factoring in the relatively poor conversion and selectivity of the chosen catalyst.